Irradiation performance of AGR-1 high temperature reactor fuel - Demkowicz, Paul A.; Hunn, John D.; Ploger, Scott A.; Morris, Robert N.; Baldwin, Charles A.; Harp, Jason M.; Winston, Philip L.; Gerczak, Tyler J.; van Rooyen, Isabella J.; Montgomery, Fred C.; Silva, Chinthaka M. (Nuclear engineering and design, 2016)
•Post-irradiation examination was performed on AGR-1 coated particle fuel.•Cesium release from the particles was very low in the absence of failed SiC layers.•Silver release was often substantial, and varied considerably with temperature.•Buffer and IPyC layers were found to play a key role in TRISO coating behavior.•Fission products palladium and silver were found in the SiC layer of particles. The AGR-1 experiment contained 72 low-enriched uranium oxide/uranium carbide TRISO coated particle fuel compacts in six capsules irradiated to burnups of 11.2 to 19.6% FIMA, with zero TRISO coating failures detected during the irradiation. The irradiation performance of the fuel including the extent of fission product release and the evolution of kernel and coating microstructures was evaluated based on detailed examination of the irradiation capsules, the fuel compacts, and individual particles. Fractional release of 110mAg from the fuel compacts was often significant, with capsule-average values ranging from 0.01 to 0.38. Analysis of silver release from individual compacts indicated that it was primarily dependent on fuel temperature history. Europium and strontium were released in small amounts through intact coatings, but were found to be significantly retained in the outer pyrocarbon and compact matrix. The capsule-average fractional release from the compacts was 1×10−4 to 5×10−4 for 154Eu and 8×10−7 to 3×10−5 for 90Sr. The average 134Cs fractional release from compacts was <3×10−6 when all particles maintained intact SiC. An estimated four particles out of 2.98×105 in the experiment experienced partial cesium release due to SiC failure during the irradiation, driving 134Cs fractional release in two capsules to approximately 10−5. Identification and characterization of these particles has provided unprecedented insight into the nature and causes of SiC coating failure in high-quality TRISO fuel. In general, changes in coating morphology were found to be dominated by the behavior of the buffer and inner pyrolytic carbon (IPyC), and infrequently observed SiC layer damage was usually related to cracks in the IPyC. Palladium attack of the SiC layer was relatively minor, except for the particles that released cesium during irradiation, where SiC corrosion was found adjacent to IPyC cracks. Palladium, silver, and uranium were found in the SiC layer of irradiated particles, and characterization of these elements within the SiC microstructure is the subject of ongoing focused study.